A survey on computer hardware awareness of UP BLIS students - Mendoza, Richard F. (2003)
Information technology explosion is the trend today and no one can stop this phenomena. In the field of librarianship our institution is adapting to computerization. Library services are computer-based and some UP BLIS courses use computers. This was the basis of the researcher for this study.